The Effect of Auditor Ethics, Auditor Experience and Independence on Audit Quality Through Professional Skepticism - Farida, Farida (Atestasi : Jurnal Ilmiah Akuntansi, 2021)
This study aims to assess the impact of auditor ethics, auditor experience, and auditor independence on the quality of audits, with skepticism acting as an intervening variable. The study comprised a cohort of 52 auditors operating in Jakarta. The data source utilized in this study consists of primary data acquired through disseminating questionnaires to all participants. The planned data analysis procedure involves conducting tests on the outer model, inner model, and hypothesis utilizing structural equation modeling (SEM) analysis with smartPLS. The findings indicated that auditors' ethical conduct, level of expertise, independence, and skepticism had a favorable and noteworthy impact on the quality of audits. Auditors' ethical conduct, professional expertise, and impartiality exert a constructive and substantial influence on the level of skepticism. Concurrently, auditors' ethical conduct, professional background, and impartiality positively influence the quality of audits by fostering a critical mindset.